Disruption of INOS, a Gene Encoding myo-Inositol Phosphate Synthase, Causes Male Sterility in Drosophila melanogaster. - Jackson, N.A.M.; Flores, A.M.; Eldon, E.D.; Klig, L.S. (G3 : genes - genomes - genetics, 2018)
Inositol is a precursor for the phospholipid membrane component phosphatidylinositol (PI), involved in signal transduction pathways, endoplasmic reticulum stress, and osmoregulation. Alterations of inositol metabolism have been implicated in human reproductive issues, the therapeutic effects of drugs used to treat epilepsy and bipolar disorder, spinal cord defects, and diseases including diabetes and Alzheimer's. The sole known inositol synthetic enzyme is myo-inositol synthase (MIPS), and the homolog in Drosophilia melanogaster is encoded by the Inos gene. Three identical deletion strains (inos?DF /CyO) were constructed, confirmed by PCR and sequencing, and homozygotes (inos?DF /inos?DF ) were shown to lack the transcript encoding the MIPS enzyme. Without inositol, homozygous inos?DF deletion fertilized eggs develop only to the first-instar larval stage. When transferred as pupae to food without inositol, however, inos?DF homozygotes die significantly sooner than wild-type flies. Even with dietary inositol the homozygous inos?DF males are sterile. An inos allele, with a P-element inserted into the first intron, fails to complement this male sterile phenotype. An additional copy of the Inos gene inserted into another chromosome rescues all the phenotypes. These genetic and phenotypic analyses establish D. melanogaster as an excellent model organism in which to examine the role of inositol synthesis in development and reproduction.